Osteocalcin Regulates Arterial Calcification Via Altered Wnt Signaling and Glucose Metabolism. (29th October 2019) - Rashdan, Nabil A; Sim, Alisia M; Cui, Lin; Phadwal, Kanchan; Roberts, Fiona L; Carter, Roderick; Ozdemir, Derya D; Hohenstein, Peter; Hung, John; Kaczynski, Jakub; Newby, David E; Baker, Andrew H; et al.
ABSTRACT: Arterial calcification is an important hallmark of cardiovascular disease and shares many similarities with skeletal mineralization. The bone‐specific protein osteocalcin (OCN) is an established marker of vascular smooth muscle cell (VSMC) osteochondrogenic transdifferentiation and a known regulator of glucose metabolism. However, the role of OCN in controlling arterial calcification is unclear. We hypothesized that OCN regulates calcification in VSMCs and sought to identify the underpinning signaling pathways. Immunohistochemistry revealed OCN co‐localization with VSMC calcification in human calcified carotid artery plaques. Additionally, 3 mM phosphate treatment stimulated OCN mRNA expression in cultured VSMCs (1.72‐fold, p < 0.001). Phosphate‐induced calcification was blunted in VSMCs derived from OCN null mice ( Ocn −/− ) compared with cells derived from wild‐type (WT) mice (0.37‐fold, p < 0.001). Ocn −/− VSMCs showed reduced mRNA expression of the osteogenic marker Runx2 (0.51‐fold, p < 0.01) and the sodium‐dependent phosphate transporter, PiT1 (0.70‐fold, p < 0.001), with an increase in the calcification inhibitor Mgp (1.42‐fold, p < 0.05) compared with WT. Ocn −/− VSMCs also showed reduced mRNA expression of Axin2 (0.13‐fold, p < 0.001) and Cyclin D (0.71 fold, p < 0.01), markers of Wnt signaling. CHIR99021 (GSK3β inhibitor) treatment increased calcium deposition in WT and Ocn −/− VSMCs (1 μM, p < 0.001). Ocn −/− VSMCs, however, calcified less than WT cells (1 μM; 0.27‐fold, p < 0.001). Ocn −/− VSMCs showed reduced mRNA expression of Glut1 (0.78‐fold, p < 0.001), Hex1 (0.77‐fold, p < 0.01), and Pdk4 (0.47‐fold, p < 0.001). This was accompanied by reduced glucose uptake (0.38‐fold, p < 0.05). Subsequent mitochondrial function assessment revealed increased ATP‐linked respiration (1.29‐fold, p < 0.05), spare respiratory capacity (1.59‐fold, p < 0.01), and maximal respiration (1.52‐fold, p < 0.001) in Ocn −/− versus WT VSMCs. Together these data suggest that OCN plays a crucial role in arterial calcification mediated by Wnt/β‐catenin signaling through reduced maximal respiration. Mitochondrial dynamics may therefore represent a novel therapeutic target for clinical intervention. © 2019 American Society for Bone and Mineral Research.